Detection of fires in the toilet compartment and driver sleeping compartment of buses and coaches—Installation considerations based on full scale tests. (May 2016) - Willstrand, Ola; Brandt, Jonas; Svensson, Robert
Highlights: Smoke detectors in the ceiling has problem detecting some fire scenarios. Smoke detectors are generally much faster than heat detectors. High air flow does not affect aspirating detectors as much as point detectors. Abstract: Effective fire detection systems properly installed in bus and coach toilet compartments and driver sleeping compartments may save human lives and property loss. Rapid detection allows for early evacuation and extinguishment of a small fire, while late or no detection may allow the fire to spread. The purpose of the work presented in this paper is to provide recommendations on how to install fire detection systems in toilet compartments and driver sleeping compartments. The recommendations also cover what type of detection system is most suited. As a basis for the recommendations, full scale fire tests were performed with different detection systems. The fire tests were conducted in realistic mockups of a toilet compartment and a sleeping compartment. Different heat and smoke detection systems were analyzed at different positions for different fire scenarios to provide information on how to best install detection systems in these compartments. Five different scenarios were run and the most interesting finding was that two realistic fire scenarios in the toilet compartment did not activate fire detectors in the ceiling at realistic air flow rates. It is very rare that fire detectors are placed anywhere else than on the ceiling in toilet compartments on buses and the fire would then be very large upon detection.